Now You See It, Now You Don’t: A Theory of Machine Consciousness Must Explain Illusions - Simmons, Gabriel (Proceedings of the AAAI Symposium Series, 2026)
As machine intelligences become more sophisticated, individuals and societies will encounter myriad attributions of consciousness to machines. Some of these attributions may be correct; many will be illusory. This paper argues that computationalist functionalist theories of machine consciousness can and should seek to explain illusions of machine consciousness. A theory that accounts for illusions reduces the risk of producing false positives—theories that explain merely the appearance of consciousness rather than genuine consciousness. Further, given the consequential nature of consciousness attributions, whether veridical or illusory, such a theory helps society navigate issues of blame and recourse when mistaken attributions cause harm.